"I Want to Speak to a White Person": Daily Microaggressions and Resilient Leadership. (December 2021) - Cyr, Daron; Weiner, Jennie; Burton, Laura
This case study blends the accounts of 10 Black women who engaged in a research study on their experiences of microaggressions when serving as school leaders, to tell the story of one Black female principal in a mostly White suburban district. We describe the ways the environment enabled and perpetuated gendered racist incidents at multiple levels and detail some of the microaggressions affecting her career path, leadership, and community interactions, as well as the ways she overcomes these obstacles and persists. We contextualize this narrative in the literature around gender, race, and school leadership, in studies of gendered racism, and finally in White allyship scholarship. We conclude by posing questions around whose responsibility it is to address these issues, and the structural changes necessary to do so.